2011
DOI: 10.1161/strokeaha.111.622175
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Hypoattenuation on CT Angiography Source Images in Basilar Artery Occlusion

Abstract: on behalf of the Basilar Artery International Cooperation Study (BASICS) GroupBackground and Purpose-The posterior circulation Acute Stroke Prognosis Early CT Score (pc-ASPECTS) quantifies the extent of early ischemic changes in the posterior circulation with a 10-point grading system. We hypothesized that pc-ASPECTS applied to CT angiography source images predicts functional outcome of patients in the Basilar Artery International Cooperation Study (BASICS). Methods-BASICS was a prospective, observational regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 23 publications
1
73
2
Order By: Relevance
“…Several other prognostic factors have been described that predict a good clinical outcome in patients with acute BAO receiving recanalization therapy and include recanalization status, baseline NIHSS score, and the extent of ischemic changes on the pretreatment imaging studies. [18][19][20][21][22] A systematic review including 316 patients in 10 IA thrombolysis studies found that recanalization was associated with a substantial reduction in mortality rates in patients with acute BAO (mortality rate of 87% in non-recanalized compared with 39% in recanalized patients; P Ͻ .001). 18 The overall recanalization rate of these 10 studies was 64%, with a 56% mortality rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other prognostic factors have been described that predict a good clinical outcome in patients with acute BAO receiving recanalization therapy and include recanalization status, baseline NIHSS score, and the extent of ischemic changes on the pretreatment imaging studies. [18][19][20][21][22] A systematic review including 316 patients in 10 IA thrombolysis studies found that recanalization was associated with a substantial reduction in mortality rates in patients with acute BAO (mortality rate of 87% in non-recanalized compared with 39% in recanalized patients; P Ͻ .001). 18 The overall recanalization rate of these 10 studies was 64%, with a 56% mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of early ischemic changes on pretreatment imaging studies can be used as a prognostic factor of clinical outcome in patients treated with recanalization therapy. [20][21][22] Puetz et al 20 showed that the posterior circulation ASPECTS on CT angiography source images predicts good outcome or death within 1 month in the subgroup of the BASICS registry population. Of 158 patients, 23% (18/78) of patients with a posterior circulation ASPECTS Ն8 had a good outcome, whereas 11% (9/80) of those with a posterior circulation ASPECTS Ͻ8 had a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The PRE and HIAT-2 scores are also specific to the anterior circulation. For posterior circulation stroke, a posterior circulation ASPECTS (pc-ASPECTS) has been developed, although its utility may be mitigated by limitations of CT imaging of the posterior fossa [45, 46]. Incorporation of the pc-ASPECTS performed on CT or pre-ET MRI imaging into pre-intervention prognostic model has not been performed.…”
Section: Can Current Pre-intervention Prognostic Scores Be Improved?mentioning
confidence: 99%
“…score 18,19 with 1 additional slice covering the sensory and motor cortex and frontal superior gyrus. ROIs were semiautomatically positioned on the postprocessed parameter maps, and the numeric values were extracted for TTP, MTT, regional CBF (rCBF), regional CBV (rCBV), and time-to-maximum of the tissue residue function time-to-maximum.…”
Section: Image Analysismentioning
confidence: 99%